2005
DOI: 10.4319/lo.2005.50.3.1011
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobicity and reactivity of trace metals in the low‐salinity zone of a turbid estuary

Abstract: We chemically fractionated water samples from the low-salinity zone of a turbid estuary (Tamar, UK) using C18 columns to examine the controls on the complexation, hydrophobicity, and reactivity of dissolved trace metals (Co, Cu, Mn, and Pb). The hydrophobic (C18-retained) fraction of metal was related to the solubility of metal in the amphiphilic solvent, n-octanol, and in acid-base titrations and for all metals this fraction exhibited a peak centered around pH 7-8 in both freshwater and brackish water. In fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…However, while the consequences of aqueous phase disequilibria on the adsorption of metals to natural solids have been observed, they do not appear to have been quantitatively or systematically addressed. For example, in several field studies it has been noted that adsorption of many complexing metals is not accompanied by reestablishment of the original aqueous speciation ( , ), at least within the time scale of experiments or measurements (on the order of a few hours to several days). Moreover, in controlled laboratory experiments, the extent of removal of strongly complexing metals by natural sorbents is dramatically reduced following a period of preequilibration of metal in the aqueous phase ( , ); thus, different apparent solid−aqueous phase equilibria arise that depend on the sequence of reactant introduction.…”
Section: Introductionmentioning
confidence: 99%
“…However, while the consequences of aqueous phase disequilibria on the adsorption of metals to natural solids have been observed, they do not appear to have been quantitatively or systematically addressed. For example, in several field studies it has been noted that adsorption of many complexing metals is not accompanied by reestablishment of the original aqueous speciation ( , ), at least within the time scale of experiments or measurements (on the order of a few hours to several days). Moreover, in controlled laboratory experiments, the extent of removal of strongly complexing metals by natural sorbents is dramatically reduced following a period of preequilibration of metal in the aqueous phase ( , ); thus, different apparent solid−aqueous phase equilibria arise that depend on the sequence of reactant introduction.…”
Section: Introductionmentioning
confidence: 99%
“…One exception is the work of Turner and Mawji who used C-18 and liquid-liquid extractions to quantify and characterise the hydrophobic fraction of dissolved metals in natural waters. [23] Their octanol-water partition coefficients indicated that the hydrophobicity of metal complexes was both pH-and metal-dependent, [24,25] reaching a maximum in the range of pH 7-8, where the overall charge of the metal complexes was thought to be very low. Some of the metal complexes with dissolved organic matter (DOM) were also shown to be hydrophobic, and their prevalence was related to the nature, origin and concentration of the DOM [26] (Box 1).…”
Section: Introductionmentioning
confidence: 99%
“…The assertion that, in natural waters, hydrophobic species are conserved during the partition process is supported by independent measurements of the hydrophobic fraction of various trace metals in river and estuarine waters using solid-phase C18 extraction ( , ). Here, the hydrophobic fraction of dissolved metal has been observed to decrease following the addition of suspended particles, implying that hydrophobic species preferentially (ad)sorb to suspended particles.…”
Section: Resultsmentioning
confidence: 98%